ChemInform Abstract: A Three‐Step Synthesis of the Guaianolide Ring System. Issue 3 (January 2015) - Hullaert, Jan; Laplace, Duchan R.; Winne, Johan M.
Abstract The tricyclic sesquiterpene ring system is constructed by Ga(OTf)3‐catalyzed cycloaddition.